2019
DOI: 10.3390/w11061176
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Flats Morphodynamics: A new Conceptual Model to Predict Their Evolution over a Medium-Long Period

Abstract: The morphological evolution of tidal flats has been widely investigated in recent years as it represents a very important topic which is highly related to the climate-driven environmental changes. The period over which geomorphological changes can be noted is a multi-year up to pluri-decennial time scale, defined as medium-long period. This work presents a new conceptual model which is able to predict and estimate a limit depth between an erosion condition and a no-erosion condition for tidal flats. The domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…This factor can vary The results of the performed simulations showed that the sediment transport dynamics in the Lignano nearshore is predominately influenced by high intensity and low frequent wind events instead of more frequent and lower intensity ones. The same happens inside the Marano and Grado lagoon and similar contexts [20,34], for which waves generated by wind speeds greater than 10 m/s play the dominant role in sediment transport mechanisms. Following these considerations and the duration curve of the higher wind velocities depicted in Figure 9b The duration of each wind class, over an average year, has been estimated on the above-defined curve and the summary is proposed in Table 1.…”
Section: Wind Inputmentioning
confidence: 60%
See 3 more Smart Citations
“…This factor can vary The results of the performed simulations showed that the sediment transport dynamics in the Lignano nearshore is predominately influenced by high intensity and low frequent wind events instead of more frequent and lower intensity ones. The same happens inside the Marano and Grado lagoon and similar contexts [20,34], for which waves generated by wind speeds greater than 10 m/s play the dominant role in sediment transport mechanisms. Following these considerations and the duration curve of the higher wind velocities depicted in Figure 9b The duration of each wind class, over an average year, has been estimated on the above-defined curve and the summary is proposed in Table 1.…”
Section: Wind Inputmentioning
confidence: 60%
“…According to this scheme, the energy regime that governs the coastal area in front of the Marano and Grado lagoon can be defined through the mean tidal range and the mean wave height. The mean tidal range, given by the difference between the mean high water level (MHWL) and the mean low water level (MLWL) is about 0.76 m as results from the analysis carried out by Petti et al [20,34]. The mean wave height close to the Lignano tidal inlet is about 0.6 m as deduced from a 30-year-long wave simulation carried out by Benatazzo et al [35] who reproduced the present average wave climate of the Adriatic Sea.…”
Section: Study Site and Historical Analysismentioning
confidence: 87%
See 2 more Smart Citations
“…They are really important phenomena in the sediment resuspension mechanism of coastal lagoons, sheltered estuarine basins, and shallow lakes [3][4][5][6][7][8][9][10]. In these contexts, where depth limits both current velocities and the relative bottom shear stresses, locally generated waves trigger the main morphological processes [11][12][13][14]. Extended literature considers the importance of wave-induced morphodynamic changes [15][16][17] and their impact on environment also from an ecological and socio-economic point of view [18][19][20].…”
Section: Introductionmentioning
confidence: 99%